Logic Analysis of Arrhythmia Triggered by Pacemaker Special Functions - An Educational Presentation - Liu,Yi (2021)
Abstract Dual-chamber pacemaker is a fully automatic pacemaker with the function of simulating human physiological pacing. It regulates pacing by programming different refractory periods and various special functions, which are closely related to arrhythmia. After in-depth understanding of these special functions, regular electrocardiogram follow-up analysis is required to provide individualized optimal program control and so is appropriate the administration of the pacemaker’s special functions to better provide optimal clinical guidance for patients with arrhythmia.